Anticoagulation and Spine Surgery. Issue 1 (January 2020) - Porto, Guilherme B. F.; Jeffrey Wessell, DO; Alvarado, Anthony; Arnold, Paul M.; Buchholz, Avery L.
Study Design: Literature review. Objective: Preoperative management of therapeutic anticoagulation in spine surgery is critical to minimize risk of thromboembolic events yet prevent postsurgical complications. Limited research is available, and most guidelines are based on drug half-lives. We aim to clarify current guidelines and available evidence for safe practice of spine surgery in this patient population. Methods: A literature search in PubMed was done encompassing comprehensive search terms to locate published literature on anticoagulation and spine surgery. Predefined inclusion and exclusion criteria were applied and data extraction was performed. Results: A total of 17 articles met the final inclusion criteria. Of these, 12 articles were retrospective chart reviews, 3 were prospective observational studies, and 2 were systematic reviews. Current practice suggests holding warfarin until international normalized ratio <1.4, anti-Xa drugs for 48 to 72 hours, 12 to 24 hours for low-molecular-weight heparin, and 4 to 24 hours for heparin, before surgery. Antiplatelet agents can be stopped for 1 to 3 days prior to operation (81-500 mg) but must be stopped for 1 week for doses >1 g/d. For Plavix, 5 to 7 days of discontinuation advised to prevent complications. Conclusions: This review provides an overview of main anticoagulation agents seen in preoperative setting for spine patients. Although data is mixed and no true randomized control trials are available, there is growing evidence suggesting the aforementioned guidelines are needed to optimize anticoagulation in setting of spine surgery. Further studies are needed to elucidate risk of complications while operating under therapeutic levels of anticoagulation for a variety of comorbid conditions.